MOLECULAR IDENTIFICATION OF PSYCHROTROPIC BACTERIA FROM ANTARCTIC SOIL - HARUNA, ISMAIL; USMAN, NAZEEF IDRIS; ADAMU, ALIYU (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
Antarctic environment is one of the most fragile ecological systems on the earth planet. Literature indicated that a large number of reviews on diversity of microbes in cold environments often begin with a lamentation on the inadequate information about organisms that leave in cold areas or their ways of adaptation to such environments. Our objective was to identify psychrotrophic bacteria from Top cliff soil collected from Antarctica. Bacterium was isolated by incubating the sample in Antarctic Bacterial Medium in the laboratory at 20oC for 48 hours. Promega, USA DNA purification kit was used to extract the bacterial DNA. Universal eubacterial primers 27F and 1492R were used to amplify the 16S rRNA gene of the bacteria. The Amplified genes were sequenced and analysed using the basic local alignment search tool (BLAST) to identify the bacterium with highest similarity and phylogenetic tree was contrusted using clustalX. Results of the gel electrophoresis of the PCR product produced DNA fragment bands of approximately 1500bp. The isolate share 97% similarity with the top match in the GENBANK. Bacillus species were found having highest percentage similarity with the isolated bacterium from Antarctic. The 16S rRNA partial gene sequence of the psychptrophic bacterium isolated in this study was successfully deposited in GenBank nucleotide database by direct submission and receive the KX000297 accession number.